THE DEVELOPMENT OF TEACHING MATERIALS INTERACTIVE MULTIMEDIA-BASED ON CHEMICAL BONDING FOR STUDENTS OF GRADE X AT SEKOLAH MENENGAH ATAS NEGERI 1 INDRALAYA UTARA - F. EKA SAFITRI; FUAD ABD. RACHMAN; HARTONO HARTONO (Sriwijaya University Learning and Education International Conference, 2016)
The purpose of the research are to produce teaching materials valid and practicalmultimedia-based and had effectivity towards students’ learning output on chemicalbonding grade X. The methodology used in this research was development researchby using Alessi and Trollip models whichcarried out in three phases, namelyplanning, design, and development. The validity was tested by alpha test, thepractice of the teaching materials was tested by using betha test, whereas theeffectivity of the learning output was tested by field test on the real class. The resultof field test showed that the students’ learning output increase 44,37 with theaverage of the pretest score 32,19, meanwhile the result of the posttest was 76,56with N-gain score 0,65 ( mid category). The conclusion of the research was that theteaching materials interactive multimedia-based that was developed was valid,practical and had effectivity towards students’ learning output. The suggestion forother researcher, it is that they are expected to develop quiz and games for metalbonding, random question for evaluation process, and closing evaluation program inorder that the evaluation would not be able to be opened by the students before thetime;(2) for the teacher, it is expected that the teaching material will be able to beapplied as one of the teaching material in order the learning process would be easier;(3) for the school, it is expected that the teaching material interactive multimedia –based will be used as a learning resources in the teaching chemistry at X grade andas a model for other teacher.